Features of Vsevold Zaderatsky’s Polyphonic Thinking in the Cycle “24 Preludes and Fugues” - Postovoitova, Svitlana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of research. The work of Vsevolod Zaderatsky appears as a unique phenomenon, unusual in all its aspects, starting from the historical context (conditions of creation, years of oblivion, revival, publication and performance) and ending with the smallest details hidden in the inner logic of the musical work. The specifics of the thematic organization of fugues and the innovative interpretation of other elements of the fugue require special attention. The need to fully incorporate the first great polyphonic cycle in the music of the 20th century into artistic and performing practice actualizes the need to see it as a holistic phenomenon, which prompts detailed study in various analytical projections. The purpose of the article to analyze the features of Vsevolod Zaderatsky's polyphonic thinking in the cycle "24 Preludes and Fugues". Methods. In the article systematic and historical research methods are used. The results and conclusions. Undoubtedly, the main prospect of further scientific research of the cycle is its introduction into performance practice, because understanding the deep processes of polyphonic music is the key to successful performance interpretation. "24 Preludes and Fugues" by Vsevolod Zaderatskyi is a unique work in many aspects. The cycle combined traditional and innovative features, which predicted several new directions for the development of the 20th century fugue. The fugue underwent a significant transformation at various levels, and first of all, at the level of polyphonic thematic due to the specific scale and the principle of monothematic. The changes affected not only the theme of the fugue, but also other components of the fugue: countresubjects and episodes. The structural factors of the overall structure changed, the functionality of the sections, where the main trend was the expansion of the boundaries of the developing section and the desire for end-to-end development. The analysis of dramaturgical principles allows us to state that the composer managed, thanks to a single idea, to build a multidimensional structure with end-to-end dramaturgy, starting with its smallest element, the theme, and ending with the interaction of small cycles among themselves.